Die Auferstehung Jesu denken: Ostern zwischen Glaubensgrund und Glaubensgegenstand - Schärtl, Thomas (Theologie und Philosophie, 2020)
The paper discusses the crucial hermeneutical options we have to approach the Easter narratives and raises the question whether the christological burden of proof should be put on the resurrection of Christ exclusively. It also votes for a middle position (between a number of extremes) which puts the burden of proof on a variety of experiences with Jesus of Nazareth. Alongside these considerations the paper tries to determine the core of the Easter experiences as disclosure experiences. The notion of the presence of the resurrected Christ in time is modeled on the basis of some key concepts which have been recently discussed in the so-called Extended Mind-View.